Interplay Between Non-Canonical NF-κB Signaling and Hepatitis B Virus Infection - Lu, Xinyu; Chen, Qianhui; Liu, Hongyan; Zhang, Xiaoyong (Frontiers in Immunology, 2021)
The non-canonical nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway is an important component of NF-κB transcription complex. Activation of this pathway mediates the development and function of host immune system involved in inflammation and viral infection. During hepatitis B virus (HBV) infection, there is a complex interaction between infected hepatocytes and the immune cells, which can hinder antiviral immune responses and is associated with pathological changes in liver tissue. Consistently, the host immune system is closely related to the severity of liver damage and the level of viral replication. Previous studies indicated that the non-canonical NF-κB signaling pathway was affected by HBV and might play an important regulatory role in the antiviral immunity. Therefore, systematically elucidating the interplay between HBV and non canonical NF-κB signaling will contribute the discovery of more potential therapeutic targets and novel drugs to treat HBV infection.